Inculcating collaborative practice among healthcare professionals: initiative from hospital Universiti Malaysia Sabah - Jeanny John; Joanne Justin; Dainah Francis; Helen Benedict Lasimbang; Wendy Diana Shoesmith; Loo, Jiann Lin; Pang, Nicholas Tze Ping (Malaysian Journal of Medicine and Health Sciences, 2020)
Introduction: Collaborative working culture is an important milestone to be inculcated in a hospital setting. In the process of preparation for the upcoming teaching hospital of Universiti Malaysia Sabah (HUMS), the organisational value of innovative, collaborative, compassionate, empowering, and sustainable needs to be inculcated to the both management and clinical staffs. The objective of this study was to assess the efficacy of a collaborative practise workshop in staff. Methods: A two days experiential learning workshop was conducted to deliver and inculcate the organisational value of HUMS to 32 existing and newly recruited healthcare professionals, which include doctor, nurses, assistant medical officer, dental assistant, pharmacist, and radiographer. The topics consisted of principles of collaborative practice, skill of validation, feedback-giving method, approach for value identification and goal setting, reflective practice, public communication during crisis, shared decision making, and organisational problem solving. Different delivery methods include round table discussion, role play, and group work were used. Innovative real time practice of giving feedback to the management was performed directly to the hospital chief executive officer and chief clinical officer. Results: Immediate feedback from the participants found that the candidates found the course was enriching and it helped them to develop an alternative perspective on how to get work done. The staffs expressed their idea, concern, and expectation more openly with the method learned using what they had learnt. The limitation included the challenge of transition from previous working culture to new environment without further supervision. Conclusions: Further systematic evaluation using more detailed assessment tool is needed to understand the long term efficiency and translatability of the learning outcomes into clinical practice once the hospital is ready.